2008
DOI: 10.1098/rstb.2008.0277
|View full text |Cite
|
Sign up to set email alerts
|

Independence and interdependence in collective decision making: an agent-based model of nest-site choice by honeybee swarms

Abstract: Condorcet's jury theorem shows that when the members of a group have noisy but independent information about what is best for the group as a whole, majority decisions tend to outperform dictatorial ones. When voting is supplemented by communication, however, the resulting interdependencies between decision makers can strengthen or undermine this effect: they can facilitate information pooling, but also amplify errors. We consider an intriguing non-human case of independent information pooling combined with com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
130
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(138 citation statements)
references
References 23 publications
8
130
0
Order By: Relevance
“…Independence and interdependence in the nest-site choice by honeybee swarms: agent-based models, analytical approaches and pattern formation In a recent paper List, Elsholtz and Seeley [List et al 2009] have devised an agent-based model of the the nest-choice dynamics in swarms of honeybees, and have concluded that both interdependence and independence are needed for the bees to reach a consensus on the best nest site. We here present a simplified version of the model which can be treated analytically with the tools of statistical physics and which largely has the same features as the original dynamics.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 4 more Smart Citations
“…Independence and interdependence in the nest-site choice by honeybee swarms: agent-based models, analytical approaches and pattern formation In a recent paper List, Elsholtz and Seeley [List et al 2009] have devised an agent-based model of the the nest-choice dynamics in swarms of honeybees, and have concluded that both interdependence and independence are needed for the bees to reach a consensus on the best nest site. We here present a simplified version of the model which can be treated analytically with the tools of statistical physics and which largely has the same features as the original dynamics.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…These rates of finding the different nests will be taken to fulfill k α=1 π α < 1, and we will set π 0 = 1 − k α=1 π α . Throughout this paper we will follow [List et al 2009] and assume that the π α , α = 1, . .…”
Section: A Original Model By List Et Almentioning
confidence: 99%
See 3 more Smart Citations